Cambridge IELTS 17 : general training with answers : authentic practice tests. (Cambridge University Press, 2022)
"Authentic examination papers from Cambridge Assessment English provide perfect practice because they are EXACTLY like the real test. Inside IELTS 16 General Training with Answers with Audio you'll find FOUR complete examination papers plus details of the different parts of the test and the scoring system, so you can familiarise yourself with the General Training test format and practise your exam technique. Download the audio for the Listening tests, example Speaking test video, answer keys with extra explanations and sample Writing answers (instructions on inner front cover), or access your audio and video directly via QR codes in the book"--Publisher's description.